2019
DOI: 10.1088/2040-8986/ab42bd
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic pulse generation in short fiber amplifiers

Abstract: The evolution of a laser pulse in a normal dispersion fiber amplifier is studied numerically. The cases of amplification with ideal spectrally flat gain and amplification with spectrally parabolic gain are considered. It is shown that the transformation of the input pulse envelope into parabolic form is possible, not only for spectrally flat but also for spectrally limited gain. In the last case, the important parameter is the optimal length of the amplifier. The results show that for a sufficiently broadband … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…One of the effects accompanying USP propagation is the modulation instability (MI) that can be employed both for USP generation and control of USP repetition rate [15,[25][26][27][28][29]. In this process, the light evolution exhibits periodic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…One of the effects accompanying USP propagation is the modulation instability (MI) that can be employed both for USP generation and control of USP repetition rate [15,[25][26][27][28][29]. In this process, the light evolution exhibits periodic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Self-similar parabolic pulse generation in single-mode fibers (SMFs), first predicted in 1993 by Anderson et al (1993) and then demonstrated in 2000 by Fermann et al (2000), has been widely investigated and is still an active area of research due to its unique characteristics and numerous applications for potential scaling approach of fiber laser systems to unprecedented pulse energy and power levels (Kruglov et al 2002;Hirooka and Nakazawa 2004;Finot et al 2006Finot et al , 2007Boscolo et al 2008;Ghosh et al 2009;Iakushev et al 2012;Biswas et al 2016;Liu et al 2017;Chowdhury et al 2019;Schukarev et al 2019). Such pulse is an attractor solution to the nonlinear Schrödinger equation (NLSE) in a normal dispersion regime with the presence of nonlinearity.…”
Section: Introductionmentioning
confidence: 99%